2013
DOI: 10.1002/jssc.201201144
|View full text |Cite
|
Sign up to set email alerts
|

The study of enantioselectivity of all regioisomers of mono‐carboxymethyl‐β‐cyclodextrin used as chiral selectors in CE

Abstract: This work documents the influence of the position of single carboxymethyl group on the β-cyclodextrin skeleton on the enantioselectivity. These synthesized monosubstituted carboxymethyl cyclodextrin (CD) derivatives, native β-cyclodextrin, and commercially available carboxymethyl-β-cyclodextrin with degree of substitution approximately 3 were used as additives into the BGE consisting of phosphate buffer at 20 mmol/L concentration, pH 2.5, and several biologically significant low-molecular-mass chiral compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…In the present work, all the CE separations were carried out with 20 mmol/L sodium phosphate buffer, pH 2.5, as the BGE. This electrolyte was chosen because of our positive experience as we reached successful enanatioseparations of TB using all the monosubstituted CDs previously . TB is positively charged at such pH (p K a 4.75) and degree of dissociation of the monosubstituted carboxymethyl‐CDs (p K a 3.6) is very limited .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, all the CE separations were carried out with 20 mmol/L sodium phosphate buffer, pH 2.5, as the BGE. This electrolyte was chosen because of our positive experience as we reached successful enanatioseparations of TB using all the monosubstituted CDs previously . TB is positively charged at such pH (p K a 4.75) and degree of dissociation of the monosubstituted carboxymethyl‐CDs (p K a 3.6) is very limited .…”
Section: Resultsmentioning
confidence: 99%
“…Beside the studies on persubstituted CD derivatives there are also papers focused on the enantioselectivity of monosubstituted CDs. In such case three isomers may exist substituted at the position C2, C3, or C6, respectively . The results revealed that both the position of carboxymethyl group within the CD skeleton and the size of the CD cavity strongly influenced the enantioseparation ability of these selectors toward the studied analytes.…”
Section: Introductionmentioning
confidence: 95%
“…Org. [78,82,83,85,[108][109][110] Per-O-methyl-2 A -O-carboxymethyl--CD was prepared from per-O-methyl-2 A -O-allyl--CD by oxidation with NaIO 4 /RuCl 3 [83] or from per-O-methyl-2 A -O-formylmethyl--CD with NaClO 2 /NaH 2 PO 4 [111] and also by treatment of permethylated 2 A -O-hydroxy--CD with iodoacetate. 2016, 5322-5334 www.eurjoc.org achieved with LiH in DMSO together with a catalytic amount of LiI.…”
Section: Synthesis Of Derivatives Substituted At Positionmentioning
confidence: 99%
“…[78,82,83,85,[108][109][110] 3 A -O-Formylmethyl--CD was synthesised from 3 A -O-cinnamyl--CD by reductive ozonolysis (O 3 /Me 2 S). [78,82,83,85,[108][109][110] 3 A -O-Formylmethyl--CD was synthesised from 3 A -O-cinnamyl--CD by reductive ozonolysis (O 3 /Me 2 S).…”
Section: Synthesis Of Derivatives Substituted At Positionmentioning
confidence: 99%
See 1 more Smart Citation